GAMBARAN PENGETAHUAN ORANG TUA TENTANG IMUNISASI CAMPAK DI WILAYAH KERJA - Benidetus C. S; Maria H. Bakri; Abdul Majid (Caring : Jurnal Keperawatan, 2017)
Measles is still a disease that has the highest case in the city of Yogyakarta. 41 positive case of measles in 2015, while in 2016 the number increased to 144 cases. In 2016 from 14 sub-districts, the highest incidence was in the work area of Puskesmas Umbulharjo I with 24 cases of positive measles increased compared to the previous year as many as 5 cases. However, the coverage of measles immunization has been more than 98% by 2015, which already exceeds the national target of 90%. The research aims to determine the description of parents knowledge about measles immunization in the area of Umbulharjo Puskesmas 1. The research design was quantitative descriptive with survey method in work area of Umbulharjo 1 Public Health Center in 2017. The sample technique used was simple random sampling, with total sample of 68 respondents. The research used of questionnaires as a data collection tool. Variable used was single variable that was parents knowledge about immunization of measles. The research results show the characteristics of respondents were most common at the age of 24-29 years (45.31%), senior high school education (60.94%), mostly unemployed (32.81%), and 53.13% had never received information related measles immunization. Respondents who have received information related to measles immunization mostly (76.67%) obtained from counseling. The result of description parents knowledge about measles immunization in working area of Puskesmas Umbulharjo I is 20,31% had good knowledge, 43,75% had enough knowledge, and 35,94% had less knowledge. Based on the results, it can be concluded that the obtained a description of parents' knowledge about measles immunization in the area of Puskesmas Umbulharjo I with sufficient category.